The Effects of activities designed with three-dimensional printing technology on science education - Avinal, Merve; Aydin, Abdullah (Firtina Academy, 2022)
The aim of this study is to investigate the effectiveness of the activities designed with 3D printing technology on the teaching of the sixth-grade systems in our body unit and to determine the views of students on this technology.  In this study, a mixed research design in which quantitative and qualitative research methods are used together was preferred.  A total of 60 sixth grade students participated in the study. The study was carried out for 6 weeks and within the scope of a science lesson. During the study, lessons in the experimental group were processed using the activities developed with 3D printing technology in addition to the current curriculum while lessons in the control group were processed using the 2018 Science Curriculum. Data were then analyzed using the SPSS statistics program and descriptive analysis. The findings of the study revealed that there was a significant difference between the post-test mean scores for academic achievement in the experimental and control groups. It can be said that the activities developed with the 3D printing technology used in the teaching of the subjects in the experimental group after the application increased the academic achievement compared to the teaching in the control group where the current program was used. The results obtained from the qualitative findings of the research also support these quantitative results. It is recommended to use more 3D printing technology in science education.